Carlos Villa and the Intergrity of Spaces - Gonzalves, Theodore S.; Machida, Margo; Johnson, Mark Dean; Berkson, Bill; Roth, Moira; Goldberg, David A.M. (California : Meritage Press, 2011)
Kunsteducatie, immigratie, multiculturalisme
boek
Keywords: Villa, Carlos